2023
DOI: 10.3390/fermentation9060525
|View full text |Cite
|
Sign up to set email alerts
|

Adaptive Laboratory Evolution of Bacillus subtilis 168 for Efficient Production of Surfactin Using NH4Cl as a Nitrogen Source

Abstract: Bacillus subtilis strain 168 is commonly used as a host to produce recombinant proteins and as a chassis for bio-based chemicals production. However, its preferred nitrogen source is organic nitrogen, which greatly increases production costs. In this study, adaptive laboratory evolution (ALE) was used to improve B. subtilis 168 growth using NH4Cl as the sole nitrogen source. The cell density (OD600) of a mutant strain LJ-3 was 208.7% higher than that of the original strain. We also optimized the metal ions in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 33 publications
0
4
0
Order By: Relevance
“…For example, utilizing single-component inorganic nitrogen sources, such as ammonium sulfate, ammonium nitrate, etc ., would demonstrate a significant advantage in terms of lowering costs of the fermentation and facilitating the process evaluation. 58 Second, it is reported that most auxotrophic strains showed decreased cell growth and production capacity during the biosynthesis process. 59 To promote the overproduction of homoeriodictyol, future efforts should be made in complementing the auxotrophic markers of the engineered strain.…”
Section: Resultsmentioning
confidence: 99%
“…For example, utilizing single-component inorganic nitrogen sources, such as ammonium sulfate, ammonium nitrate, etc ., would demonstrate a significant advantage in terms of lowering costs of the fermentation and facilitating the process evaluation. 58 Second, it is reported that most auxotrophic strains showed decreased cell growth and production capacity during the biosynthesis process. 59 To promote the overproduction of homoeriodictyol, future efforts should be made in complementing the auxotrophic markers of the engineered strain.…”
Section: Resultsmentioning
confidence: 99%
“…In our pursuit to harness this adaptability for biotechnological applications, we employed ALE to improve the galactose utilization capability of B. subtilis . There were several trials to engineer B. subtilis with ALE (Driessen et al 2023 ; Li et al 2023 ; Zeigler and Nicholson 2017 ). Zhang et al have reported that B. subtilis was adapted under xylose as a selection pressure and validated several key mutations (Zhang et al 2015 ).…”
Section: Discussionmentioning
confidence: 99%
“…Zhang et al have reported that B. subtilis was adapted under xylose as a selection pressure and validated several key mutations (Zhang et al 2015 ). ALE was utilized not only to address carbon stress but also to promote rapid development, efficient use of nitrogen sources, and tolerance to lignocellulosic hydrolysate (Driessen et al 2023 ; Li et al 2023 ; Liu et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation